2014
DOI: 10.1371/journal.pone.0087920
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Differential Expression of microRNAs in Ovaries of Laying and Broody Geese (Anser cygnoides) by Solexa Sequencing

Abstract: BackgroundRecent functional studies have demonstrated that the microRNAs (miRNAs) play critical roles in ovarian gonadal development, steroidogenesis, apoptosis, and ovulation in mammals. However, little is known about the involvement of miRNAs in the ovarian function of fowl. The goose (Anas cygnoides) is a commercially important food that is cultivated widely in China but the goose industry has been hampered by high broodiness and poor egg laying performance, which are influenced by ovarian function.Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
(49 reference statements)
3
22
0
Order By: Relevance
“…The sequencing data were analysis as described previously by Xu et al 5 First, the low-quality reads were removed. For the analysis of their distribution, the remaining sequences (clean reads) were mapped to the zebrafish genome using SOAP (http://soap.genomics.org.cn/) with a tolerance of one mismatch.…”
Section: Sequencing Data Analysis and Identification Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequencing data were analysis as described previously by Xu et al 5 First, the low-quality reads were removed. For the analysis of their distribution, the remaining sequences (clean reads) were mapped to the zebrafish genome using SOAP (http://soap.genomics.org.cn/) with a tolerance of one mismatch.…”
Section: Sequencing Data Analysis and Identification Of Mirnasmentioning
confidence: 99%
“…1 More and more studies have revealed that miRNAs play important roles in many different biological processes, such as proliferation, metabolism, apoptosis, oncogenesis, and immunity. [2][3][4][5] The process of spermatogenesis is very complicated. 6 Recent findings showed that miRNAs were expressed in a developmental stage-specific manner during spermatogenesis, which suggested that these miRNAs might participate in male germ cell development.…”
Section: Introductionmentioning
confidence: 99%
“…Another report on miR169 in Arabidopsis found that up‐regulation of the miR169 family initiates stress‐induced early flowering by inhibiting the target gene encoding transcription factor AtNF‐YA (Xu et al . ). The up‐regulated miRNAs, miR398a and miR398b, in the cultivar library are predicted to target RNA binding family (RRM/RBD/RNP) protein genes mediating inhibition through target cleavage.…”
Section: Discussionmentioning
confidence: 97%
“…P ‐value formula:p(x/y)=)(N2N1y(x+y)!x!y!(1+N2N2)(x+y+1)Cfalse(yyminfalse|xfalse)=false∑y=0yytrueminpfalse(yfalse|xfalse)Dfalse(yymaxfalse|xfalse)=false∑yytruemaxpfalse(yfalse|xfalse) where N 1 represent total number of clean reads, x is normalised expression level of the given miRNA from the wild cardamom sRNA library, N 2 total number of clean reads and y is the normalised expression level of a given miRNA in the cultivar sRNA library (Xu et al . ,b).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reviewed the critical roles played by miRNAs in controlling the expression of genes essential for folliculogenesis and early embryogenesis11121314. Significant efforts have been made to identify ovarian miRNAs using microarrays or high-throughput sequencing1516171819. However, no comprehensive overview on the ovarian miRNome is available.…”
mentioning
confidence: 99%